Opposite actions of dopamine on aversive and appetitive memories in the crab - Klappenbach, Martín (2012)
The understanding of how the reinforcement is represented in the central nervous system during memory formation is a current issue in neurobiology. Several studies in insects provide evidence of the instructive role of biogenic amines during the learning and memory process. In insects it was widely accepted that dopamine (DA) mediates aversive reinforcements. However, the idea of DA being exclusively involved in aversive memory has been challenged in recent studies. Here, we study the involvement of DA during aversive and appetitive memories in the crab Chasmagnathus. We found that DA-receptor antagonists impair aversive memory consolidation, in agreement with previous reports in insects, while administration of DA facilitates memory formation after a weak training protocol. In contrast, DA treatment during appetitive training was found to impair formation of long-term appetitive memory. In addition, as a first step in elucidating the neuroanatomical correlates of DA action on memory, we mapped dopaminergic neurons in the central nervous system of the crab. Results of the current study, together with those obtained in a previous work about the role of octopamine (OA), suggest that both amines (DA and OA) play a dual action in memory processes. On the one hand, DA and OA mediate the aversive and the appetitive signals, respectively, throughout training, while on the other hand, they interfere with the formation of memory of the opposite sign (DA in appetitive and OA in aversive). Our results support a new understanding about the way appetitive and aversive stimuli are processed during memory formation to ensure adaptive behavior.